MOTIVATION EFFECTS, RESPONSIBILITIES, SATISFACTION AND MAJOR SATISFACTION WITH TEACHER'S PERFORMANCE IN DUTA MAS VOCATIONAL SCHOOLS, JAKARTA - Prayogi, Dwi; Ikatrianasari, Zulfa Fitri (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2020)
Education is an institution that has an important role in improving the quality of human resources. Based on this phenomenon, it is important to consider the problem of Motivation, Discipline, Job Satisfaction with the performance of teachers in Duta Mas Jakarta, because motivation and work discipline can influence job satisfaction and teacher performance. . In this study PLS-SEM approach is used. PLS-SEM aims to test predictive relationships between constructors or latent variables by looking at whether there is a relationship or influence between these constructions, so that the pathway has no significant effect. From the results and analysis of the data presented and explained, states the motivation, discipline, and job satisfaction of teachers towards the achievement of teachers. This is shown from the calculation of